2003
DOI: 10.1080/10635150390218187
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Phylogeny of the New Zealand Short-Tailed Bat Mystacina tuberculata Inferred from Multiple Mitochondrial Gene Sequences

Abstract: An intraspecific phylogeny was established for the New Zealand short-tailed bat Mystacina tuberculata using a 2,878-bp sequence alignment from multiple mitochondrial genes (control region, ND2, 12S ribosomal RNA [rRNA], 16S rRNA, and tRNA). The inferred phylogeny comprises six lineages, with estimated divergences extending back between 0.93 and 0.68 million years to the middle Pleistocene. The lineages do not correspond to the existing subspecific taxonomy. Although multiple lineages occur sympatrically in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…For example, studies by Lloyd (2003aLloyd ( , 2003b found New Zealand's endemic Short-tailed Bat contains six distinct mitochondrial lineages that probably diverged in the mid-Pleistocene owing to allopatric fragmentation. The North Island lineages show evidence of population expansion and the mixing in the central region of the Island but the distribution remains consistent with an isolation-by-distance dispersal model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies by Lloyd (2003aLloyd ( , 2003b found New Zealand's endemic Short-tailed Bat contains six distinct mitochondrial lineages that probably diverged in the mid-Pleistocene owing to allopatric fragmentation. The North Island lineages show evidence of population expansion and the mixing in the central region of the Island but the distribution remains consistent with an isolation-by-distance dispersal model.…”
Section: Discussionmentioning
confidence: 99%
“…Flying forest birds (e.g. parakeets: Boon et al 2001a;Australasian robins: H. C. Miller 2003, unpublished data;kokako: Murphy et al 2006;wood pigeons: J. Goldberg 2008, unpublished data) and the endemic short-tailed bat (Lloyd 2003) also have low levels of genetic variation among populations, suggesting they too suffered intense bottlenecking during the Mid-to Late Pleistocene. Cicadas of the genus Kikihia are found throughout New Zealand in many lowland habitats and several species have moved into the sub-alpine region, but none are alpine.…”
Section: The Sistersmentioning
confidence: 99%
“…Despite their ability to fly, they show relatively high levels of genetic structuring, probably related to their diversified social organization systems: for example, Myotis bechsteinii, Myotis myotis, Macroderma gigas and Mystacina tuberculata (Worthington Wilmer et al, 1999;Kerth et al, 2000;Lloyd, 2003;Ruedi and Castella, 2003). The exceptions are the few migratory species, whose populations are typically poorly subdivided for example, Tadarida brasiliensis and Pteropus sp.…”
Section: Introductionmentioning
confidence: 99%